A new species of the genus Graphelmis DELÈVE, 1968 from China (Coleoptera: Elmidae) - Dong, Xue; Bian, Dongju (Zootaxa, 2020)
Graphelmis dulongensis sp. nov. is described from Yunnan, China. Photos of habitus and male genitalia are given.